Scales of critically stable few-body halo systems - Frederico, T.; Yamashita, Marcelo Takeshi [UNESP] (Elsevier B.V., 2007)
We review the scaling properties of few-body observables near the critical conditions for binding, with particular attention to light exotic nuclei, molecules and ultracold atoms.